THE ROLE OF TEACHER IN THE DEVELOPMENT OF READING LITERACY - Fransiska Jaiman Madu; Mariana Jediut (Jurnal Cakrawala Pendas, 2023)
The problem of low reading literacy in the Ruá Catholic Primary School (SDK) was the motivation for this study. The purpose of this study is to describe the role of teachers at SDK Ruá in the development of students' reading literacy. This type of research is qualitative, using data collection techniques through interviews, observation and documentation. The techniques of data collection, data reduction, data presentation and inference (verification) developed by Miles and Huberman were used for data analysis. On the basis of the results of the study, the teachers at SDK Ruá have fulfilled their role and have played an important role in overcoming the main problem related to the low level of reading literacy. The efforts made are to get the pupils used to reading independently, to create a reading corner, to maximise learning by directing the formation of reading literacy, to provide non-text books that the pupils like, and to maximise the use of learning media. Based on the results of the study, it can be concluded that the teachers at SDK Ruá have performed their role optimally. This can be seen from the habits of the students and the physical evidence seen in the school regarding the procurement of books that the students like and the creation of a reading corner. Penelitian ini dilatarbelakangi oleh permasalahan terkait rendahnya literasi membaca di Sekolah Dasar Katolik (SDK) Ruá. Penelitian ini bertujuan untuk mendeskripsikan peran guru di SDK Ruá dalam mengembangkan literasi membaca siswa. Jenis penelitian ini merupakan kualitatif dengan menggunakan teknik pengumpulan data melalui wawancara, observasi, dan dokumentasi. Analisis data menggunakan teknik yang dikembangkan Miles dan Huberman yaitu pengumpulan data, reduksi data, penyajian data, penarikan kesimpulan (verifikasi). Berdasarkan hasil penelitian, guru di SDK Ruá telah menjalankan perannya dan mengambil bagian penting dalam mengatasi masalah utama terkait rendahnya literasi membaca. Upaya yang dilakukan adalah membiasakan siswa untuk membaca secara mandiri, membuat pojok baca, memaksimalkan pembelajaran dengan mengarahkan pada pembentukan literasi membaca, pengadaan buku-buku nonteks yang disukai siswa, dan memaksimalkan penggunaan media pembelajaran. Berdasarkan hasil penelitian, dapat disimpulkan bahwa guru-guru di SDK Ruá telah menjalankan perannya dengan maksimal dan hal ini terlihat dari kebiasaan para siswa dan bukti fisik yang terlihat di sekolah terkait pengadaan buku-buku yang disukai siswa dan pembuatan pojok baca.